Holocentric Chromosomes Probably Do Not Prevent Centromere Drive in Cyperaceae - Krátká, Marie; Šmerda, Jakub; Lojdová, Kateřina; Bureš, Petr; Zedek, František (Frontiers in Plant Science, 2021)
Centromere drive is an evolutionary process initiated by centromeric repeats expansion, which leads to the recruitment of excess kinetochore proteins and consequent preferential segregation of an expanded centromere to the egg during female asymmetric meiosis. In response to these selfish centromeres, the kinetochore protein CenH3 adaptively evolves to restore chromosomal parity and counter the detrimental effects of centromere drive. Holocentric chromosomes, whose kinetochores are assembled along entire chromosomes, have been hypothesized to prevent expanded centromeres from acquiring a selective advantage and initiating centromere drive. In such a case, CenH3 would be subjected to less frequent or no adaptive evolution. Contrary to this expectation, we found positive selection acting on the CenH3 gene among 35 species from the holocentric plant family Cyperaceae whose frequency is comparable to monocentric clades with asymmetric female meiosis. This suggests that kinetochore structure in Cyperaceae does not prevent centromere drive. This could be explained by the possibility that centromeres in Cyperaceae do not have kinetochores assembled along the entire chromosome during meiosis; instead, they might have a polycentric structure, which has been observed in the genus Rhynchospora to date. We propose that preventing centromere drive is not the primary purpose of holocentric chromosomes, and their ability to suppress it likely depends on their kinetochore structure in meiosis.